2011
DOI: 10.3402/ejpt.v2i0.8749
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adaptation to life-threatening injury in dyads: the role of dysfunctional disclosure of trauma

Abstract: BackgroundCertain modes of trauma disclosure have been found to be associated with more severe symptoms of posttraumatic stress (PTS) in different trauma populations: the reluctance to disclose trauma-related thoughts and feelings, a strong urge to talk about it, and physical as well as emotional reactions during disclosure. Although social-contextual influences gain more and more interest in trauma research, no study has yet investigated these “dysfunctional disclosure tendencies” and their association with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 50 publications
4
20
1
1
Order By: Relevance
“…Men were more reluctant to disclose traumatic events. These results are in line with the previous studies that revealed gender differences in posttraumatic stress reactions (18) and disclosure of trauma (19). We also found gender differences in types of experienced traumatic events, which might be closely related to gender differences in trauma disclosure and social acknowledgment.…”
Section: Discussionsupporting
confidence: 93%
“…Men were more reluctant to disclose traumatic events. These results are in line with the previous studies that revealed gender differences in posttraumatic stress reactions (18) and disclosure of trauma (19). We also found gender differences in types of experienced traumatic events, which might be closely related to gender differences in trauma disclosure and social acknowledgment.…”
Section: Discussionsupporting
confidence: 93%
“…In a sample of political prisoners, DTQ scales showed good internal consistency (α = .82 -.88) and test-retest reliability (r tt = .76 - Müller & Maercker, 2000). The short-form had previously also demonstrated good psychometrics (Pielmaier & Maercker, 2011). For the present sample, it achieved good internal consistency, Cronbach α = .84.…”
Section: Methodsmentioning
confidence: 63%
“…Dysfunctional Disclosure was measured using the Disclosure Questionnaire (Mueller & Maercker, 2006) in an abbreviated form (Pielmaier & Maercker, 2011). The 12 items can be divided into three subscales: urge to talk, reluctance to talk , and emotional reactions while disclosing .…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the quality of social support resources seems to influence the psychological adjustment outcome after stress exposure (Ajrouch, Abdulrahim, & Antonucci, 2013; Brewin, Andrews, & Valentine, 2000). Disclosure of stressful experiences has been shown to facilitate recovery from severe stress (Freedman, Gilad, Ankri, Rozier, & Shalev, 2015; Pennebaker, 1989; Pielmaier & Maercker, 2011). The third level includes societal and cultural factors.…”
Section: Socio-interpersonal Model Of Stress-response Syndromesmentioning
confidence: 99%